Colorectal cancer among farmers in the AGRICAN cohort study. (June 2022) - Talibov, Madar; Tual, Séverine; Morlais, Fabrice; Meryet-Figuière, Matthieu; Boulanger, Mathilde; Bouvier, Véronique; Perrier, Stephanie; Clin, Bénédicte; Baldi, Isabelle; Lebailly, Pierre; ,; Dabakuyo-Yonli, S.; et al.
Abstract: Objectives: Specific farming types and tasks have rarely been studied in relation to colorectal cancer (CRC). We evaluated associations between 5 types of livestock and 13 types of crops in relation to CRC and its subsites within the Agriculture and Cancer (AGRICAN) study. Methods: AGRICAN cohort includes 181, 842 agricultural workers living in 11 French geographical areas. Data on farming types and tasks was collected by self-administered questionnaires. We identified 2 609 CRC, 972 right colon, 689 left colon and 898 rectal incident cancer cases during follow-up from 2005 to 2015. Cox proportional hazards models were used to estimate hazard ratios (HR) and 95% confidence intervals (95% CI). Results: Significantly increased CRC risk was observed for farmers producing horses (HR=1.18, 95% CI 1.06–1.31), sunflower (HR=1.23, 95% CI 1.03–1.45) and field vegetables (HR=1.18, 95% CI 1.02–1.36). Positive associations were also observed for pig, poultry and wheat/barley. Some associations were observed only for specific subsites: left colon cancer was associated with fruit growing (HR=1.36, 95% CI 1.09–1.70) and potato (HR=1.28, 95% CI 1.05–1.57). Tasks related to livestock (animal care, insecticide treatment, disinfection of milking equipment and building) or to crop (haymaking, sowing, pesticide treatment, seed treatment, harvesting) were also associated with CRC. Duration and size of farming types/task increased the risk for some of the associations. Analysis stratified by sex suggested an interaction with several farming types/task. Conclusions: The current study showed original and positive findings for several farming types and tasks and CRC risk, overall and by subsites. Highlights: Associations between farming, pesticides and colorectal cancer (CRC) have been poorly studied. This is a comprehensive assessment of associations between farming types/tasks and CRC. CRC risk among farmers is associated with the livestock and crop type, specific tasks, and varies by CRC subtype.